KESEHATAN DALAM PERSPEKTIF HINDU: PENTINGNYA PENELITIAN ILMIAH TERHADAP OBAT-OBATANTRADISIONAL BALI - I Putu Eryn Pranatha (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Traditional Balinese medicine, known as Usadha or Balian, has deep roots in Hindu beliefs and philosophy. In this context, health is seen as a balance between body, mind and spirit, which is in line with Hindu concepts such as karma, reincarnation and chakras. This study aims to explore the importance of scientific research on traditional Balinese medicines to understand their potential and benefits in modern medicine. Through a literature review, this article sheds light on the history and basic elements of Usadha, as well as the potential for integration of traditional and modern medicine. Scientific research on traditional Balinese medicines is considered important for investigating the health claims and safety of using these medicines, promoting the recognition and preservation of traditional knowledge, and supporting traditional medicine as part of cultural and health heritage. Furthermore, this study confirms the importance of further research to help preserve and develop this traditional knowledge, while integrating it with modern medicine to achieve better outcomes in health and healing